2021
DOI: 10.1080/13880209.2021.1990357
|View full text |Cite
|
Sign up to set email alerts
|

Clinacanthus nutans attenuates atherosclerosis progression in rats with type 2 diabetes by reducing vascular oxidative stress and inflammation

Abstract: Context Atherosclerosis predisposes individuals to adverse cardiovascular events. Clinacanthus nutans L. (Acanthaceae) is a traditional remedy used for diabetes and inflammatory conditions. Objectives To investigate the anti-atherosclerotic activity of a C. nutans leaf methanol extract (CNME) in a type 2 diabetic (T2D) rat model induced by a high-fat diet (HFD) and low-dose streptozotocin. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…Antioxidant activity has been proved to be relevant in the treatment of Alzheimer’s disease [ 19 ], diabetes [ 20 ], hypertension [ 21 ], lung fibrosis [ 22 ], and tumors [ 23 ]. Therefore, natural products possessing antioxidant activity may present a complementary alternative for the treatment of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant activity has been proved to be relevant in the treatment of Alzheimer’s disease [ 19 ], diabetes [ 20 ], hypertension [ 21 ], lung fibrosis [ 22 ], and tumors [ 23 ]. Therefore, natural products possessing antioxidant activity may present a complementary alternative for the treatment of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that HFD-induced hyperlipidemia results in a significant increase in serum TC, TG, LDL-C, and AI [ 23 , 24 , 41 ]. The present study demonstrated that TRF for six weeks reduced the levels of TC, TG, LDL-C, and AI in obese rats.…”
Section: Discussionmentioning
confidence: 99%
“…Serum total cholesterol (TC), triglycerides (TG), and high-density lipoprotein-cholesterol (HDL-C) were measured using the colorimetric method with Integra 800 automatic immunoanalyzer (Roche Diagnostic Sytems, Manheim, Germany). The serum LDL-C was calculated using Friedwald formula [ 24 ], as follows: LDL-C = TC − (HDL-C + TG/5) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely recognized that chronic low-level inflammation caused by hyperglycemia and dyslipidemia is a key pathological mechanism that exacerbates diabetic atherosclerosis [ 24 ]. After 12 weeks of BJJ therapy, the expressions of FBG, TC, TG, and LDL-C were reduced, while HDL-C was elevated, confirming our earlier research [ 17 ].…”
Section: Discussionmentioning
confidence: 99%